Christianity and Literature. Figures of the (Ig)Noble (Colloquia Comparativa Litterarum, 2025)
Kalin Mikhaïlov. Christianity and Literature. Figures of the (Ig)Noble. Sofia, St. Kliment Ohridski University Press, 2023, ISBN: 978-954-07-5726-1.